Factors Influencing Women’s Satisfaction in Beauty Parlour Business - Karna, Sanjoy Kumar (Butwal Campus Journal, 2020)
This study investigates the factors influencing satisfaction of women entrepreneurs associated with beauty parlour business in Butwal sub-metropolitan city of Rupandehi district of Nepal. Using a sample of 50 beauty parlours in the study area and applying Probit Model, the results show that the probability of BPE's satisfaction decreases by 0.103 for those who have relatively big family. The probability of BPE's satisfaction increases by 0.0186 for those who are married. The probability of BPE's satisfaction increases by 0.049 for those whose husbands are helpful. The probability of BPE's satisfaction increases by 0.096 for those who think that society has positive attitude towards BPB. The probability of BPE's satisfaction increases by 0.2 for those who think that BPB has decreased discrimination against woman. The study reveals that the beauty parlour business can enhance the women’s satisfaction by enabling them contributing to their families in fulfilling the household demands.